Gaya Kepimpinan Pemimpin dan Komitmen Pekerja di Jabatan Agama Islam Selangor - Baharudin, Othman (2004)
The purpose of this study is to investigate the relationship between leadership styles of the director and commitment level of the subordinate in Jabatan Agama Islam Selangor. The styles of leadership studied are transformational and transactional. The study was also to find out if there were any differences in commitment level based on the leadership style of their directors. Besides, the study also to find out if, there were any differences in leadership styles and commitment level based on the demographical characteristics of subordinates i.e gender, categories of age, job level and level of education. A total of 373 subordinate were chosen by simple random sampling and participated in the study The Multifactor Leadership Questionaire (MLQ) was used to measure the leadership style of the directors while An Organizational Commitment Questionaire (OCQ) was used to measure the level of commitment of the subordinate. These two psychometric tools were tested for their relevanve and reliability. The collected data was analyzed by using the t-test, One Way ANOVA and Pearson Correlation and the resulting data were further analyzed using the descriptive statistics and the inferential statistics. The findings of this stuf shows that there is a significant relationship between leadership styles of a director and the level of commitment of subordinates. Based on each dimensions, the result shows charismatic leadership has a high positive significant compared to the other components i.e individualized consideration, intellectual stimulation, contingent reward and management-by-exception with the level of commitment of subordinates. The findings also show that there are no significant between leadership styles and levels of commitment of subordinates based on their demographic characteristics.